The evaluation of bottled water quality compliance association formal and informal retailers in Gauteng municipality. South Africa - J.L. Maselela; M.I. Mokgobu; L.S. Mudau (Applied Food Research)
The quality of bottled water (BW) can vary based on factors such as handling, processing, transportation, hygiene practices, and the retail shop from which it is purchased. This study aimed to compare the microbiological quality of BW (Heterotrophic plate count (HPC), E.coli, and total coliforms (TC)) purchased from both formal and informal retail shops. The study used a convenience sampling approach and categorized the shops into formal and informal. A total of 117 samples were obtained, with 16 from informal shops and 101 from formal shops. The data was analysed using SPSS version 29, and the water quality compliance was assessed based on SANS 241, 1657, and World Health Organization standards for drinking water. The findings indicated a significant link between compliance with bottled water (BW) standards and the specific shop from which the BW was purchased (p 0.001). These results highlight shop compliance's crucial role in influencing BW's microbiological quality, especially in relation to total coliforms (TC) and E.coli presence. Bottled water obtained from informal shops did not meet the standards, whereas BW from formal shops adhered to the standards for TC and E.coli.